Keynote Speech by the H.E. Mr N. Enkhbayar, President of Mongolia at the Inauguration Session of the "Ulaanbaatar Forum for East Asia" - Enkhbayar, Nambaryn (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i13.3 Mongolian Journal of International Affairs No.13 2006 pp.7-12